Strategi Bersaing untuk Mempertahankan Eksistensi Usaha Kecil - Khusnia Latifatul Mauna; Siswahyudianto (Idarotuna : Journal of Administrative Science, 2022)
The food and beverage industry sector is an advantage for Indonesia's economic progress, which has prospects for development. The more enthusiasts, the tighter the competition in the beverage industry, so every business must have a competitive strategy to maintain business existence in the face of competition. Mbak Endah's Classic Nyoklat Ice is a business that still exists in the face of competition. Based on these assumptions, it is the author's interest the aim to research the Es Nyoklat Classic business, which is a beverage business that is quite well known for its existence while still having many customers and enthusiasts among many contemporary beverage business competitors and being able to survive in the face of competition. This study uses a qualitative descriptive method interpreted as a method to describe a research result that aims to provide a description, explanation, and validation of the phenomenon being studied. From the study results, it can be seen that the competitive strategy applied in maintaining existence is by looking at the business environment, creating product diversity, carrying out attractive product packaging, and determining product segmentation on Mbak Endah's Classic Ice Nyoklat.